2019
DOI: 10.1177/0890117119878074
|View full text |Cite
|
Sign up to set email alerts
|

Practical Nutrition Knowledge Mediates the Relationship Between Sociodemographic Characteristics and Diet Quality in Adults: A Cross-Sectional Analysis

Abstract: Purpose: To investigate the direct and indirect effects of sociodemographic/health factors on diet quality through practical nutrition knowledge (PNK) about how to compose a balanced meal. Design: A cross-sectional study using data from an online survey of the 10 000 Steps cohort (data collected November-December 2016). Setting: Australia. Participants: Adults (n = 8161). Response rate was 16.7%. Measures: Self-reported lifestyle, health, and sociodemographic characteristics, including diet quality and PNK. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Here, it was found that the probability of having a poor or moderate diet quality was greater in adults with CMD with a lower educational level compared with those without CMD with higher education. This is not the first time that a higher educational level has been associated with good dietary habits [97][98][99], although some studies have failed to find any association [100] or even found an inverse link [101,102], probably due to people with a higher educational level having access to better knowledge about food [103,104]. In addition, some studies have shown that a favorable attitude towards a healthy diet was associated with a higher educational level [105][106][107].…”
Section: Main Findingsmentioning
confidence: 94%
“…Here, it was found that the probability of having a poor or moderate diet quality was greater in adults with CMD with a lower educational level compared with those without CMD with higher education. This is not the first time that a higher educational level has been associated with good dietary habits [97][98][99], although some studies have failed to find any association [100] or even found an inverse link [101,102], probably due to people with a higher educational level having access to better knowledge about food [103,104]. In addition, some studies have shown that a favorable attitude towards a healthy diet was associated with a higher educational level [105][106][107].…”
Section: Main Findingsmentioning
confidence: 94%
“…Considering the growing evidence of an association between greater fruit and vegetable consumption during childhood and reduced chronic diseases in adulthood [13][14][15][16], both short-and long-term implications of programs that successfully increase fruit intake among children are likely to be significant. However, public health initiatives should not only address deficits in nutrition knowledge [17,18], but also enduring challenges with regard to the access to and affordability of fresh, high-quality fruits-particularly among low-income children [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…37 The present study showed that those with less education had a lower diet quality score than those with higher education, which is consistent with findings in other diseases such as diabetes mellitus 38 and heart disease. 39 Individuals with high education levels are more likely to learn about healthy behaviors, including nutrition and dietary guidelines, 40 and higher education may also lead to higher income and better access to grocery stores with a wide range of healthy foods. 41,42 Diet quality generally improves with income level, 10 because fresh produce and other healthy foods tend to be more expensive than fast foods and unhealthy foods.…”
Section: Discussionmentioning
confidence: 99%